PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BEI - Mawardi, M. Cholid (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2013)
Abstract; This research was aimed to investigate the effect of corporate govenance corelated with the compositions of board of independent directors, the size of director boards, audit committee and the size of the company to profit management happened in banking company listed in Indoonesia stoct exchange. In this research, profit management was measured by acrual estimate management ditected by Healy model (1985). This model was thedevelopment of acrual prediction model with measuring estimate acrual as the total acrual (Dechhow et al. 1995).The population of thisresearchwas alltheIndonesianbanking companies listed in Indonesian stoct exchange since 2008-2010. The data of corporate govenance and profit management were got from annual report, finance accounts of each company got from legitimate site of Indonesian stoct axchange (www.idx.co.id). The analyzedcompanieswere 84 (28x3) bankingcompanieslistedinIndonesianstoctexchangesince 2008-2010, andthe sampling methodusedinthisresearchwas purposive sampling. The hypothesis of thisresearchwas testedbydoubled linear regresion. The result of the testing thehypothesiswas shownthatcorporategovenance variable correlated with compositions of board of independent directors,the size of director boards, audit committee and the size of the company simultaneously didn’t correlate to the stoct exchange. Key words: Corporate Governance, Board of Independent Directors, The Size of Director Boards, Audit Committee, The Size of the Company, and Stoct Exchange. ABSTRAK Aimed this research was to investigate the effect of corporate govenance corelated with the Compositions of the board of independent directors, the size boards of directors, audit committee and the size of the company to profit happened in banking management company listed in Indoonesia stoct exchange. In this research, profit management was a Measured by acrual estimate ditected management models by Healy (1985). This Model was the development of prediction models with measuring acrual acrual estimate as the total acrual (Dechhow et al. 1995). The population of this research was all the banking companies listed in Indonesian Indonesian exchange stoct since 2008-2010. The data is of corporate govenance and profit management were got from the annual report, finance accounts of each company got from the legitimate site of Indonesian stoct axchange (www.idx.co.id). The Analyzed companies were 84 (28x3) companies listed in Indonesian banking stoct exchange since 2008 to 2010, and the sampling method used in this research was purposive sampling. The hypothesis of this research was tested by linear regresion doubled. The result of the testing of the hypothesis was shown that corporate govenance Compositions of variables correlated with an independent board of directors, the size boards of directors, audit committee and the size of the company simultaneously did not correlate to the stoct exchange. Key words: Corporate Governance, Board of Independent Directors, The Size of the Director Boards, Audit Committee, The Size of the Company, and Stoct Exchange.